2011
DOI: 10.1093/brain/awr235
|View full text |Cite
|
Sign up to set email alerts
|

Gelastic epilepsy and hypothalamic hamartomas: neuroanatomical analysis of brain lesions in 100 patients

Abstract: Hypothalamic hamartomas present with isolated fits of ictal laughter (gelastic epilepsy) or a combination of gelastic and other types of seizures. Many of these patients also suffer from cognitive decline, neuropsychiatric comorbidities and precocious puberty. Although there is a large body of anecdotal evidence about hypothalamic hamartomas and gelastic seizures, many questions still remain to be answered. For instance, which specific hypothalamic regions are most affected by the location of hamartomas causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 53 publications
6
89
2
4
Order By: Relevance
“…18 Our SRT procedure had no effect on precocious puberty. In addition, some patients experienced delayed precocious puberty after SRT.…”
Section: Functional Outcomesmentioning
confidence: 67%
See 2 more Smart Citations
“…18 Our SRT procedure had no effect on precocious puberty. In addition, some patients experienced delayed precocious puberty after SRT.…”
Section: Functional Outcomesmentioning
confidence: 67%
“…20 The lower rate of freedom from non-gelastic seizures in adult patients is likely because non-gelastic seizures are caused by independent secondary epileptogenesis. Parvizi et al 18 also reported that patients with non-gelastic seizures were significantly older and had significantly longer duration of epilepsy than patients with only GS. Therefore, early surgery is important for the prevention of independent secondary epileptogenesis.…”
Section: Seizure Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…La prevalencia es de 1-2 casos/100.000 habitantes. Los HH pueden ser pedunculados, habitualmente asociados a pubertad precoz central [1][2][3] , o sésiles, relacionados con epilepsia con crisis gelásticas de difícil control 1-3 . Presentamos 4 casos de HH, 3 niños comenzaron como pubertad precoz y otro con crisis parciales complejas y crisis gelásticas.…”
unclassified
“…Existen varios estudios que demuestran la eficacia de la radiocirugía estereotáctica (cirugía con gamma-knife) con resultados similares a la cirugía convencional con disminución de la morbimortalidad 1,6 , con el inconveniente de que su efecto se evidencia más tardía-mente (6 meses tras la intervención), siendo necesarias en ocasiones varias sesiones para conseguir adecuado control clínico. 3 …”
unclassified